Application of the Informatics Stack framework to describe a population-level emergency department return visit continuous quality improvement program. (January 2020) - Taher, Ahmed; Bunker, Edward; Chartier, Lucas B.; Ostrow, Olivia; Ovens, Howard; Davis, Brittany; Schull, Michael J.
Abstract: Introduction: Population health programs are increasingly reliant on Health Information Technology (HIT). Program HIT architecture description is a necessary step prior to evaluation. Several sociotechnical frameworks have been used previously with HIT programs. The Informatics Stack is a novel framework that provides a thorough description of HIT program architecture. The Emergency Department Return Visit Quality Program (EDRVQP) is a population-level continuous quality improvement (QI) program connecting EDs across Ontario. The objectives of the study were to utilize the Informatics Stack to provide a description of the EDRVQP HIT architecture and to delineate population health program factors that are enablers or barriers. Materials and Methods: The Informatics Stack was used to describe the HIT architecture. A qualitative study was completed with semi-structured interviews of key informants across stakeholder organizations. Emergency departments were selected randomly. Purposive sampling identified key informants. Interviews were conducted until saturation. An inductive qualitative analysis using grounded theory was completed. A literature review of peer-reviewed background literature, and stakeholder organization reports was also conducted. Results: 23 business actors from 15 organizations were interviewed. The EDRVQP architecture description is presented across the Informatics Stack levels. The levels from most comprehensive to most basic are world, organization, perspectives/roles, goals/functions, workflow/behaviour/adoption, information systems, modules, data/information/knowledge/wisdom/algorithms, and technology. Enabling factors were the high rate of electronic health record adoption, legislative mandate for data collection, use of functional data standards, implementation flexibility, leveraging validated algorithms, and leveraging existing local health networks. Barriers were privacy legislation and a high turn-around time. Discussion: The Informatics Stack provides a robust approach to thoroughly describe the HIT architecture of population health programs prior to program replication. The EDRVQP is a population health program that illustrates the pragmatic use of continuous QI methodology across a population (provincial) level.